(untitled) (Annals of Medical Research, 2021)
Aim: An increasing number of patients are undergoing surgical treatment for gallbladder polyps (GPs). As there is still controversy on the subject, it remains unclear whether GPs are the precursors of gallbladder tumors. The aim of this study was to examine the clinicopathological features of patients who had undergone cholecystectomy in our clinic for the treatment of gallbladder polyps.Material and Methods: A retrospective review was made of the clinicopathological data of patients who underwent cholecystectomy, selected from a group of 2048 patients, who received treatment between 2014-2018.Results: A total of 79 (3.8%) patients were identified, comprising 50 (63.2%) females and 29 (36.8%) males with a mean age of 43 years (range, 22-81 years). During pre-operative ultrasonography, 60 (75.9%) patients were detected with a single polyp and 19 (23.1%) patients had multiple polyps. When postoperative histology was evaluated, 70 (88.6%) patients had cholesterol polyps, 2 (2.5%) patients had gallbladder stones, 5 (6.3%) patients had papillary adenomas without dysplasia and 1 (1.2%) patient had papillary adenoma with dysplasia, while 1 (1.2%) of patient had gallbladder adenocarcinoma.Conclusion: According to the results of this study, as gallbladder polyps may be pre-cancerous or cancerous lesions, patients diagnosed with GP should be followed up closely with surgical treatment applied when necessary. Keywords: Gall bladder polyps; cholecystectomy; gallbladder adenocarcinoma.